Deficiency of B vitamins in women of childbearing age, pregnant, and lactating women in Brazil: a systematic review - Tatiane Salgado Galvão de Macedo; Michel Carlos Mocellin; Simone Augusta Ribas; Michelle Teixeira Teixeira; Alessandra da Silva Pereira; Gabriel Montalvão Palermo; Cintia Chaves Curioni (Systematic Reviews)
Abstract Objective This study aimed to evaluate the prevalence of B-complex vitamin deficiencies in Brazilian women of childbearing age, pregnant women, and lactating women. Methods This systematic review analyzed cross-sectional and cohort studies published up to August 2023 and indexed in MEDLINE, SciELO, LILACS, Scopus, Embase, Web of Science, and the Brazilian Digital Library of Theses and Dissertations. Additional data were obtained by contacting researchers from Brazilian public universities. Studies assessing deficiency rates using biochemical markers were included. Two reviewers independently selected studies, extracted data, and assessed methodological quality using the Joanna Briggs Institute tool. Results Of the 3772 records identified, 13 studies were included. Only folate (n = 13), B12 (n = 11), and B6 (n = 1) deficiencies were investigated, and all studies were cross-sectional. B12 deficiency prevalence varied widely, reaching up to 29.4%. Folate deficiencies were generally low, with only one study reporting a rate as high as 37%. Other B-complex vitamins were insufficiently studied. Most studies had methodological limitations, particularly small sample sizes. The significant heterogeneity across studies limited the feasibility of a pooled quantitative meta-analysis. Conclusion There is a clear need for more robust studies across all Brazilian regions to improve understanding of vitamin deficiency rates and to support effective nutritional interventions. Systematic review registration PROSPERO CRD42020188474